Profil guru sekolah dasar dalam mengimplementasikan pembelajaran daring berbasis media aplikasi - Arumanda, Hesa Resti; Riyadi, Riyadi; Daryanto, Joko (Universitas Sebelas Maret, 2021)
This study aims to 1) find out the profile of teachers in implementing online learning based on application media 2) find out the obstacles experienced by teachers in implementing online learning based on application media. This research was conducted at SD Negeri Mangkubumen Kidul No. 16 Surakarta uses a qualitative descriptive method. The subjects of this study were teachers of class I to class VI. Data collection techniques are observation, interviews, and documentation. Learning is carried out online using the internet and media applications such as whatsapp, zoom, google form, and google meet. The learning process is carried out with due regard to teacher competency standards, namely 1) pedagogic competency standards 2) professional competency standards 3) personality competency standards 4) social competency standards. In carrying out the learning process, the teacher encountered several obstacles. However, the process of implementing online learning at SD Negeri Mangkubumen Kidul No. 16 Surakarta can be said to be quite good.